Enhanced lightweight and secure session key establishment protocol for smart home inhabitants. (4th July 2021) - Dhoot, Anshita; Manjul, Manisha; Devgan, Sonam Kaul; Nazarov, A. N.; Pankaj,
Abstract: The concept behind the wireless communication and the world of information technologies is to create an environment for the users such that they can easily access the smart lifestyle and get interacted with the social world. Session key should be secure enough as every sensor is using a small token to authenticate every network. We are proposing a new, efficient, secure and light-weight protocol in smart home environments to overcome these shortcomings. The quantity demand and investment in research and development, while the other model focuses on a more realistic relationship between the quantity demand and the price.